Responses of IPR Campos Gerais and BRS Estilo bean cultivars to different nitrogen fertilizer rates in corn (Zea mays L.) succession (Research, Society and Development, 2021)
Among the nutrients, nitrogen (N) is the element required in greater quantity by the bean plant. Depending on the cultivar, it has greater or lesser N-fixing capacity. The aim of this work was to evaluate the performance of two common bean cultivars under nitrogen topdressing in corn succession, on yield components and yield. The experiment was carried out in randomized blocks in a 2x5 factorial scheme, the first factor being the common bean cultivars (IPR Campos Gerais and BRS Estilo) and the second factor the nitrogen rates (0, 30, 60, 90 and 120 kg ha- 1), with four repetitions. At harvest, plants were collected in one meter, in the useful area of ​​each subplot to determine: number of plants per meter; number of pods/plant; number of grains/plant; number of grains/pods; mass of a thousand grains and productivity. The cultivars differed regarding the number of pods per plant, grains per plant and yield, but they were equivalent for the number of plants per meter, grains per pod and mass of a thousand grains. Comparing the production component number of pods per plant and grain yield, it is concluded that the cultivar that produced the highest number of pods per plant and showed the highest yield was BRS Estilo. There were differences between the treatments for the two cultivars, only in the yield obtained. The highest yield averages were obtained in treatments with doses above 60 kg ha-1 of N.